2013
DOI: 10.1021/bi3013214
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Activated SgrAI–DNA Oligomers Using Ion Mobility Mass Spectrometry

Abstract: SgrAI is a type IIF restriction endonuclease that cuts an unusually long recognition sequence and exhibits self-modulation of DNA cleavage activity and sequence specificity. Previous studies have shown that SgrAI forms large oligomers when bound to particular DNA sequences and under the same conditions where SgrAI exhibits accelerated DNA cleavage kinetics. However, the detailed structure and stoichiometry of the SgrAI-DNA complex as well as the basic building block of the oligomers have not been fully charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 66 publications
(206 reference statements)
2
27
0
Order By: Relevance
“…1C). This analysis shows that the low-activity SgrAI DBD that was previously characterized crystallographically (Dunten et al, 2008; Little et al, 2011; Park et al, 2010a) can oligomerize in a run-on fashion in the presence of activating DNA, supporting a current hypothesis from mass spectrometry data (Ma et al, 2013). …”
Section: Resultssupporting
confidence: 77%
“…1C). This analysis shows that the low-activity SgrAI DBD that was previously characterized crystallographically (Dunten et al, 2008; Little et al, 2011; Park et al, 2010a) can oligomerize in a run-on fashion in the presence of activating DNA, supporting a current hypothesis from mass spectrometry data (Ma et al, 2013). …”
Section: Resultssupporting
confidence: 77%
“…The exception is nucleotide CCS values, which, aside for the 2009 study from McLean and coworkers, 68 have been published in small numbers spread across several studies and years, and currently comprise about 1% all CCS values reported. 153,199209 This observation is reflected in the fact that while many of these IM-based biomolecular studies have coincided strongly with developments in MS-based lipidomics, glycomics and metabolomics, the role of mass spectrometry related techniques in genomics research is, and has always been, relatively small.…”
Section: Ccs Coverage Over Timementioning
confidence: 99%
“…The term "run-on oligomer" (ROO) filament is used here to describe an assembly of an enzyme into a filament by the successive addition of enzymes at either end, and which, in principle, could extend indefinitely (8,16). ROO filament formation by SgrAI was first proposed in 2010 based on behavior in analytical ultracentrifugation and native gels (7) and subsequently using ion-mobility mass spectrometry (17). The enzymatic activity of SgrAI was found to be activated in the ROO and to possess an altered (expanded) DNA sequence specificity (7,8).…”
mentioning
confidence: 99%